Impact of vehicular emissions on ozone levels: A comprehensive study of nitric oxide and ozone interactions in urban areas - Amaury de Souza; José Francisco de Oliveira-Júnior; Kelvy Rosalvo Alencar Cardoso; Sneha Gautam (Geosystems and Geoenvironment)
This study examines the relationship between nitric oxide (NO) concentrations and vehicular traffic, focusing on trucks and buses as key sources of NO emissions. The conversion of NO to nitrogen dioxide (NO2) influences ozone (O3) formation, with excess nitrogen oxides (NOX) limiting O3 production. Elevated O3 levels under certain conditions pose public health risks. This study analyzes seasonal and diurnal variations in NO2, NOX and O3 concentrations, accounting for meteorological factors and the impact of agricultural fires. Pearson correlation coefficients between pollutants and climatic variables were calculated, along with the ventilation coefficient (VC), to explore pollutant-atmosphere dynamics. Analysis of 2021 data revealed peak SO2, NO, NO2, NOX and O3 levels between August and October, with O3 values averaging 18 ppb (1.90–79.70 ppb range). Seasonal trends showed NOX peaks in autumn and winter, while O3 concentrations were highest in summer and spring, driven by temperature and solar radiation. Negative correlations between SO2, NO, NO2, NOX and O3 were observed (e.g., r = -0.312, p < 0.01). VC values increased from 1 p.m., peaking at 10 p.m. (2000–4500 m/s), and stabilized during early morning hours. The findings emphasize the need for integrated urban air quality management, combining vehicle emission controls and strategies to address meteorological influences and agricultural fires. Continuous monitoring and targeted policies during high-risk periods, particularly August to October, can mitigate pollutant impacts, improve air quality, and safeguard public health in urban areas.